Penilaian Konsumen mengenai pemasaran melalui Facebook - Puput Santoso; Andi Sanyoto; M. Syukri Mustofa (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2022)
Facebook is not yet familiar to use for e-commerce in Malinau Regency, because most people still prioritize buying and selling through direct face-to-face with sellers or through classified ads in newspapers, and this can result in the level of acceptance of the people of Malinau being higher in the future. low levels of e-commerce through Facebook Market Place, and online marketers have lost transaction opportunities, so the people of Malinau may be left behind when compared to other regions in e-commerce activities through Facebook Market Place. With the analysis of the achievement score on Facebook features, it resulted in a recommendation that the features on Facebook could be further developed by adding other facilities to attract the attention of respondents so that they are willing to open Facebook at least 1 hour per day for e-commerce activities